Digitalization of Islamic Finance: Epistemological Study of the National Sharia Board-Indonesian Council of Ulama’s Fatwa - Hidayati, Tri; Hidayatullah, Muhammad Syarif; Komarudin, Parman; Atika, Atika (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
The dynamic and rapid development of digital business and finance requires progressive Sharia legal certainty. National Sharia Board-Indonesian Council of Ulama (Dewan Syariah Nasional – Majelis Ulama Indonesia/DSN-MUI) has issued several fatwas related to digital finance. This research aims to examine the portrait of DSN-MUI’s progressiveness towards the digital finance paradigm and aspects of Islamic legal epistemology in the DSN-MUI Fatwa with the theme of digital finance. This research uses a qualitative approach. The primary data for this research are the DSN-MUI fatwas up to 2021 with a digital theme, plus secondary data in the form of relevant literature. Data analysis uses content analysis techniques. The findings are that there are three DSN-MUI fatwas regarding digital finance in Sharia financial institutions, namely Fatwa No. 116/DSN-MUI/IX/2017, No. 117/DSN-MUI/II/2018, and No. 140/DSN-MUI/VIII/2021. These three fatwas constitute progressive Islamic business law and are important for the Sharia financial industry in Indonesia. DSN-MUI used the ta’līlī and istiṣlāḥi methods with the consideration that electronic money, digital-based financing, and crowdfunding are permissible (mubah) based on sharia principles to achieve benefit. These three DSN-MUI fatwas need to be transformed into OJK regulations and can become a source for making derivative fatwas.